Effects of surface modified phosphate slag powder on performance of asphalt and asphalt mixture. (15th January 2018) - Qian, Guoping; Wang, Kun; Bai, Xianping; Xiao, Ting; Jin, Dazhong; Huang, Qianjin
Highlights: The application of phosphorus slag powder (PSD) is environmental friendly. The PSD modified by TM-P has good dispersibility and stability in asphalt. Phosphorus slag modified asphalt (PSMA) has excellent anti-aging property. Abstract: Phosphate type single alkyl oxygen base titanates TM-P was used to modify the surface of phosphorus slag powder in this paper. The surface characteristics and modification mechanism of phosphorus slag particles were characterized by using Scanning Electronic Microscopy (SEM). The effects and mechanism of the surface modified phosphorus slag powder to the asphalt and asphalt mixtures were analyzed by Fourier Transform Infrared Spectroscopy (FTIR), dynamic shear rheological test (DSR), Marshall test, rutting test and freeze-thaw splitting test. The results show that phosphorus slag powder modified by TM-P (10% by weight of the powder) enhance the compatibility with asphalt, resulting in the increase of anti-aging, rutting resistance and water damage resistance of asphalt mixture.